Pengaruh Model Pembelajaran Treffinger Berbantuan Media Scrapbook Terhadap Keterampilan Menulis Cerita Fabel Kelas VII - Yuliana; Sumardi, Aida (BULLET : Jurnal Multidisiplin Ilmu, 2024)
The background of this thesis writing is students’ lack writing skill ability in Indonesian language subjects, especially fable text material. In addition, the application of learning models and media that are inadequate in developing the material and activeness in the learning process. The purpose of this study was to determine the effect of the Treffinger learning model with the help of Scrapbook media on the skills of writing fable stories in class VII and the learning outcomes of students. This research was conducted at SMP Muhammadiyah 02 Rangkapanjaya, in class VII. The research method used in this study was True Experimental Design with Pretest-Posttest Group Design. The results showed the influence of the Treffinger learning model with the help of Scrapbook media on the ability of writing skills of fable stories in class VII. This is based on the results of the t-test hypothesis test there is sig 0.001 ˂ 0.05 and the value of tit 2.421˃ ttab 2.034. Therefore, Ha is accepted and H0 is rejected, meaning that there is an effect of the Treffinger learning model assisted by Scrapbook media on fable stories writing skill in class VII.